Factors associated with adolescents' smoking experience and staying tobacco free - (:unkn) unknown (My University, 2010)
Introduction It is not expected that those who did not smoke during their adolescent years will start to smoke later in life. This study was planned to learn the thoughts of Turkish adolescents about staying tobacco free. Methods A descriptive study was conducted in 2007 with 866 adolescents aged 11 to 14 years.On a self-administered questionnaire, non-smoker students answered both multiple choice and open-ended questions about why they would not smoke in the future. The Chi-square test and logistic regression analysis was used for statistical assessment. For the answers to the open-ended questions, thematic analysis was applied. Results The mean age of the participants was 12.84 ± 1.14 years. The incidence of a smoking experience at least once in the participant's lifetime was 12% and the rate of current smoking was 3.6%. The most listed reasons for staying tobacco free were health problems directly related to smoking (64%), such as 'it can cause diseases' or 'it kills', negative effects of smoking other than health (51%), such as 'it smells bad' or 'it is toxic', and some subjective judgements related only with their self perceptions, such as 'I am happy and healthy' or 'it affects growth negatively' (20%). The most well-known problem related to tobacco use was lung cancer and the least wellknownproblems were bladder cancer and chronic bronchitis. Most of the smoking students (68%) were not aware that second-hand smoking was harmful (p=0.003). There were significant correlations between smoking experience and male gender, having a smoker in the household and low educational level of the mother or the father (p=0.000, p=0.018, p=0.022, p=0.044 respectively). Conclusion We suggest that the beliefs and perceptions of adolescents about smoking should be given as much consideration as the negative effects of cigarettes in planning smoking free messages. © 2010 Radcliffe Publishing.
Keywords: Adolescent health; Health education; Perceptions; Prevention